Estudo comparativo das características de absorção sonora de painéis de fibra de açaí e juta com geometrias superficiais planas e não plana - LIMA, Naianny Matos (2020)
The urban population has lived in constant exposure to noise due to the growing and almost always disorderly process of urbanization. Currently, noise pollution is the third most polluting type that affects the planet, according to the World Health Organization (WHO), reaching about 120 million people worldwide. Harmful effects of noise on humans are detrimental to physical, mental and social well-being. Other disadvantageous effects are perceived in constructs in which acoustic criteria related to absorption, isolation and sound transmission are not adequately considered, such as in an environment with excessively high reverberation time or poor sound insulation, leading to interferences in speech comprehension or privacy. In this sense, the search for new materials, which have a low cost of acquisition and production, that contribute to acoustic comfort, has intensified in recent years. In this scenario, some vegetal fibers drawn attention, since they have been used as raw material in the manufacture of panels that present good acoustic performance, regarding sound absorption, and other advantageous characteristics (low acquisition cost, do not present risks to human health or to the environment, come from renewable sources, just to name but a few) in relation to traditional materials such as glass wool and rock wool. In the present work, panels of vegetable fibers (açaí and jute) with flat and non-flat (with triangular shapes) surface geometry were investigated in a scale model reverberant chamber. It was found that, for the same panel thickness, the non-planar geometry panels presented slightly superior performance relative to the flat surface panels, especially at medium and high frequencies (from 1600 Hz), and this is attributed to protuberances in surface. Finally, it is concluded that the geometric changes made in the non-flat surface panels contributed to increase its effective absorption area, giving rise to panels with improved acoustic performance.